ESTROGEN RECEPTORS OF HAIRS BLACKS AND WHITES - Laswati, Hening; Pangkahila, Jahja Alex (BALI MEDICAL JOURNAL, 2014)
Background: Aging is termed as same as degenerative process, in which all part of tissue organs retarted the microstructure either macrostructure, forming and function even the colour, including black hair change to white hair. Several researchers have been recommended that estrogen hormone be able ease black to white hair, but hormone without any presenting of receptor won’t be work properly. The main aim of this study were to determine amount of estrogen receptor contents in famales and males black and white hairs included the microscopically structure. Method: Twelve females and males there were 50 -56 years old each pairs black and white head hairs were plucked along with follicles. This estrogen receptors analyzed using radioreceptor binding assay there were 5mm eah hair follices including the root cutted and each pair put its in 2 ml glass tube already filled in with 500 µl 125I-estradiol and incubated in 37oC for 3 hrs. Following times were over the tube flushed twice carefully the hair won’t be flushed. Then count by putting in the gamma counter chamber for 1 minute each. The values that shown in the monitor as CPM (count per minute), recorded as receptor of estradiol. Results: Mean (±SD) sum estrogen receptor in females black and white hairs were 479.3 ± 37.5 and 387.7 ± 33.0, but significantly decreased in male black hair was 316.9±17.8 and 274.0 ± 19.8. All those pairs significantly different either female black and white hairs or male black and white hair and also significantly different among groups. Conclusion: The lowest estrogen receptors recorded in male white hairs and microstructure decreasing of melanin contents.